Land productivity and economic development: Caloric suitability vs. agricultural suitability - Oded Galor; Ömer Özak (Brown University, Department of Economics, 2015)
This paper establishes that the Caloric Suitability Index (CSI) dominates the commonly used measure of agricultural suitability in the examination of the effect of land productivity on comparative economic development. The analysis demonstrates that the agricultural suitability index does not capture the large variation in the potential caloric yield across equally suitable land, reflecting the fact that land suitable for agriculture is not necessarily suitable for the most caloric-intensive crops. Hence, in light of the instrumental role played by caloric yield in sustaining and supporting population growth, and given importance of pre-industrial population density for the subsequent course of economic development, the Caloric Suitability Index dominates the conventional measure in capturing the effect of land productivity on pre-colonial population density and the subsequent course of economic development.
Keywords: O10; O40; Q10; 330; Caloric Suitability; Agricultural Suitability; Agricultural Productivity; Land Productivity; Economic Development; Population Density